2020
DOI: 10.26719/emhj.19.048
|View full text |Cite
|
Sign up to set email alerts
|

Household disaster preparedness in the Islamic Republic of Iran: 2015 estimation

Abstract: Background: Households are the most fundamental unit of society and they need to be prepared for disasters. Aims: This study assessed the 2015 national estimation of disaster preparedness among Iranian households. Methods: Using a multi-stage cluster sampling, this study was performed on 2986 households in the catchment area of 54 public health departments in all 30 provinces of the Islamic Republic of Iran. The data collection tool was Household Disaster Preparedness Index (HDPI), which included 15 disaster p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Increasing households' preparedness in the face of disasters and participation in disaster planning is one of the strategies to achieve sustainable development. 15 According to World Health Organization's (WHO) recommendations, citizens should be empowered in terms of self-dependency, first aids, and other similar procedures to respond quickly to major incidents or disasters. 20 Generally, each society is composed of groups of stakeholders exposed to similar risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing households' preparedness in the face of disasters and participation in disaster planning is one of the strategies to achieve sustainable development. 15 According to World Health Organization's (WHO) recommendations, citizens should be empowered in terms of self-dependency, first aids, and other similar procedures to respond quickly to major incidents or disasters. 20 Generally, each society is composed of groups of stakeholders exposed to similar risks.…”
Section: Discussionmentioning
confidence: 99%
“…23 Although some studies have referred to the level of knowledge as one of the factors involved in disaster preparedness, just having sufficient knowledge cannot guarantee the performance of preparedness measures. 15 Based on the findings of Muttarak's study, participating in disaster preparedness exercises and programs increased the likelihood of taking preparedness measures. Furthermore, people with higher education levels had better learning and processing skills of abstract thinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have found that households remain unprepared for disasters, even in disaster-prone areas ( 17 ). Research from Asia ( 18 , 19 ), North America ( 20 ), New Zealand ( 21 ), Australia ( 22 ), and Africa ( 23 ), as well as from the Middle East ( 24 , 25 ), has revealed low levels of household preparedness ( 26 ). In the United States, surveys at both national and local levels consistently demonstrate that the public remains under-prepared ( 27–30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Families involved in the measures implemented for disaster preparedness have been found to be more resilient; therefore, many efforts have been made to increase family preparedness. Nevertheless, based on the studies, household preparedness levels are still low and unsatisfactory (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%